Tahfiz Teachers Strategy in Fostering Students' Qur'an Memorization - Trisusanto, Rahmadani; Rasidin, Rasidin; Shalahudin, Shalahudin (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2024)
Purpose of the study: This study aims to analyze the strategies used by tahfiz teachers in fostering student memorization, as well as their impact on the development of student memorization. Methodology: This research is a descriptive-based qualitative research with 3 respondents as research subjects. The interview method is the main method and the observation and documentation methods are complementary. The data collection technique uses interview techniques with questions regarding the implementation of the tahfiz teacher's strategy in fostering memorization of the Qur'an. While the observation method is used to strengthen or clarify the results of interviews, and the documentation method is used to find out the location and subject of research. Main Findings: (1) The Tahfiz teacher's strategy in fostering students' memorization of the Qur'an has three stages, namely: planning, implementation, and evaluation. (2) The obstacles of tahfiz teachers in fostering student memorization are students who do not understand tajweed, students who are not fluent in reading the Qur'an, lazy students to memorize memorization, sleepy and lethargic students and the difficulty of students in remembering memorization. (3) the efforts of tahfiz teachers in fostering student memorization at Ahmad Dahlan junior high school in Jambi City, namely teachers try to make students always muraja'ah, teachers always motivate students, give rewards and teachers are always patient and consistent in dealing with students who always repeat the same mistakes in memorizing the Qur'an. Novelty/Originality of this study: This study aims to fill the lack of literature regarding the Tahfiz Teacher Strategy in Fostering Student Memorization. This finding provides a new contribution to the development of more interesting and effective tahfiz learning strategies for other schools or madrasahs.